Clinical Information Systems and Artificial Intelligence: Recent Research Trends - Combi, Carlo; Pozzi, Giuseppe (Yearbook of Medical Informatics, 2019)
Objectives: This survey aims at reviewing the literature related to Clinical Information Systems (CIS), Hospital Information Systems (HIS), Electronic Health Record (EHR) systems, and how collected data can be analyzed by Artificial Intelligence (AI) techniques.Methods: We selected the major journals (11 journals) collecting papers (more than 7,000) over the last five years from the top members of the research community, and read and analyzed the papers (more than 200) covering the topics. Then, we completed the analysis using search engines to also include papers from major conferences over the same five years.Results: We defined a taxonomy of major features and research areas of CIS, HIS, EHR systems. We also defined a taxonomy for the use of Artificial Intelligence (AI) techniques on healthcare data. In the light of these taxonomies, we report on the most relevant papers from the literature.Conclusions: We highlighted some major research directions and issues which seem to be promising and to need further investigations over a medium- or long-term period.
Keywords: Survey; clinical information systems; hospital information systems; electronic health records; artificial intelligence; big data analysis